Stroke risk evaluation for patients with atrial fibrillation: Insights from left atrial appendage - Fang, Runxin; Li, Yang; Wang, Jun; Wang, Zidun; Allen, John; Ching, Chi Keong; Zhong, Liang; Li, Zhiyong (Frontiers in Cardiovascular Medicine, 2022)
Left atrial appendage (LAA) is believed to be a common site of thrombus formation in patients with atrial fibrillation (AF). However, the commonly-applied stroke risk stratification model (such as. CHA2DS2-VASc score) does not include any structural or hemodynamic features of LAA. Recent studies have suggested that it is important to incorporate LAA geometrical and hemodynamic features to evaluate the risk of thrombus formation in LAA, which may better delineate the AF patients for anticoagulant administration and prevent strokes. This review focuses on the LAA related factors that may be associated with thrombus formation and cardioembolic events.